Carrying the Weight: Athletics and Obesity in High School Football Players. (November 2019) - Berkowitz, Joshua N.; Skinner, Asheley Cockrell; Lohr, Jacob A.
This article determines the prevalence of obesity among high school football players nationwide and compares obesity between position groups of football players and across team sports. We calculate body mass index (BMI) for 391 212 males participating in baseball, basketball, football, lacrosse, and soccer, then stratify BMI into commonly accepted categories and subdivide football players by position played, comparing BMI across position groups and sports. A total of 47.4% of high school football players are healthy weight (BMI = 18.5-24.9 kg/m 2 ), 18.0% have obesity (BMI = 30-34.9 kg/m 2 : 12.4%) or class 2 obesity (BMI >34.9 kg/m 2 : 5.6%). Among linemen, 14.8% are healthy weight, 14.6% have class 2 obesity, and another 29.3% have obesity. Among non-linemen, the combined prevalence of obesity and class 2 obesity is 2.7%, comparable to other team sports. Obesity is common among high school football players, more so than among other high school athletes. Obesity and class 2 obesity are only common among linemen.